3D printed dysphagia diet using pea protein gel modified by xanthan gum with different pyruvate group content - Zhenbin Liu; Xi Chen; Meirong Ruan; Yumei Liao; Zihao Wang; Yucheng Zeng; Hongbo Li; Liangbin Hu; Haizhen Mo (Food Chemistry: X)
3D printing offers a promising solution for the increasing demand for visually appealing dysphagia diets. Xanthan gum (XG) is a critical component in various thickeners specialized for dysphagia diets, in which pyruvate group is important, but relative study remains scarce. This study tried to create 3D printed dysphagia diet using composite gels of pea protein (PPI) and XG with various pyruvate content (XG0: 5.20 %, XG1: 1.87 %, XG2: 0.54 %, XG3: 0.10 %). Results revealed that decreasing pyruvate content resulted in significant reductions of both viscosity and mechanical strength of PPI-XG gel. In particular, at a shear rate of 1 s−1, the viscosity of PPI-XG0, PPI-XG1, PPI-XG2, and PPI-XG3 gels were 714.36 Pa·s, 525.32 Pa·s, 427.32 Pa·s, and 421.16 Pa·s, respectively. The PPI-XG interaction significantly affected by pyruvate, especially concerning electrostatic interactions. The PPI-XG0 and PPI-XG1 samples exhibited excellent 3D printing performance and could be categorized into level 4-pureed dysphagia diets within IDDSI framework. This research offers valuable insights for the development of 3D printed dysphagia diets, and for the standardization of XG specialized for dysphagia diets.